Spot auto-focusing and spot auto-stigmation methods with high-definition auto-correlation function in high-resolution TEM. (25th January 2018) - Isakozawa, Shigeto; Fuse, Taishi; Amano, Junpei; Baba, Norio
Abstract : As alternatives to the diffractogram-based method in high-resolution transmission electron microscopy, a spot auto-focusing method and a spot auto-stigmation method are presented with a unique high-definition auto-correlation function. Abstract: As alternatives to the diffractogram-based method in high-resolution transmission electron microscopy, a spot auto-focusing (AF) method and a spot auto-stigmation (AS) method are presented with a unique high-definition auto-correlation function (HD-ACF). The HD-ACF clearly resolves the ACF central peak region in small amorphous-thin-film images, reflecting the phase contrast transfer function. At a 300-k magnification for a 120-kV transmission electron microscope, the smallest areas used are 64 × 64 pixels ( 3 nm 2 ) for the AF and 256 × 256 pixels for the AS. A useful advantage of these methods is that the AF function has an allowable accuracy even for a low s/n ( 1.0) image. A reference database on the defocus dependency of the HD-ACF by the pre-acquisition of through-focus amorphous-thin-film images must be prepared to use these methods. This can be very beneficial because the specimens are not limited to approximations of weak phase objects but can be extended to objects outside such approximations.